The Effect of Comparative Employee Compensation on Wage and Salary Payments - Catrin, Caterina Aruli Iskandar; Driana Leniwati; Agung Prasetyo Nugroho Wicaksono (DINASTI RESEARCH, 2023)
This research aims to determine the effect of compensation comparisons on non-financial sector companies in Indonesia listed on IDX. The population of this research is all non-financial sector companies consisting of the raw materials, manufacturing and services sectors registered on IDX for the 2019-2021 period. This study uses a quantitative approach. The data analysis technique uses panel data regression. The research results show that salary comparison has a positiive and insignificant effect on company performance. The contribution of this research is to provide information about several factors that influence employee salaries. Also in a different population compared to before, you can find out the incentives given to company employees.